Analysis of the Distribution of Chemical Compounds from Fly Ash Exposed to Weather Conditions - Sambo Aleksandra; Szymanek Arkadiusz (Chemical and Process Engineering)
The paper presents investigation results of the migration of a chemical compound contained in fly ash deposited on a dry furnace waste landfill site exposed to weather conditions. Climate conditions are able to significantly affect chemical component distribution in a block of deposited, moving chemical compounds to different depths. The main aim of the investigations was to determine the chemical component distribution of deposited fly ash in the landfill. Identification of chemical components based on XRF analysis indicated the existence of differences in both tested storage layer and the fraction of fly ash.